Front Cover: A Novel Class of N‐Sulfonyl and N‐Sulfamoyl Noscapine Derivatives that Promote Mitotic Arrest in Cancer Cells (ChemMedChem 23/2019). (22nd November 2019) - Yong, Cassandra; Devine, Shane M.; Gao, Xuexin; Yan, Angelina; Callaghan, Richard; Capuano, Ben; Scammells, Peter J.
Abstract : The Front Cover shows the natural product noscapine, which is produced by the opium poppy, Papaver somniferum . Noscapine has been used as an antitussive agent since the 1950s, but its anticancer properties and ability to inhibit tubulin polymerisation were not appreciated until the late 1990s. A number of N ‐sulfonyl and N ‐sulfamoyl noscapine derivatives have been identified with improved antiproliferative potency against various cancer cell lines (MCF‐7, PANC‐1, MDA‐MB‐435, and SK‐MEL‐5 cells). These antiproliferative effects were also maintained against drug‐resistant NCI/Adr RES cells despite their high expression of the multidrug efflux pump, P‐glycoprotein. More information can be found in the Full Paper by Peter J. Scammells et al. (DOI: 10.1002/cmdc.201900477 ) on page 1968 in Issue 23, 2019, (Photos from iStock/Getty Images by Dr Microbe & mafoto).